P‐22: Spice Model for Detection of Dynamic Threshold Voltage Shift During Failure Analysis of Oxide TFT‐Based AMD Gate Drivers. Issue 1 (May 2017) - Lee, Won-Seok; Kang, Jong-Suk; Tak, Nam-Kyun; Choi, In-Chol; Kim, Jin-Young; Han, Ji-Ung; Choi, Jin-Hyung; Mativenga, Mallory; Hwang, Man-Gyu
Abstract : We present an accelerated SmartSpice model that can detect dynamic threshold voltage shift (ΔVth )‐related failure of an oxide thin‐film transistor (TFT)‐based gate driver. Because oxide TFTs do not recover completely after application of stress (or when input is LOW), cumulative ΔVth that is induced during the HIGH of the input signal may result in failure of gate drivers. For correct failure analysis, a TFT model that can detect dynamic ΔVth is, therefore, needed for the replacement of the current TFT models that cannot account for dynamic ΔVth . The model presented herein works correctly with varying temperature and any input signal.